2017
DOI: 10.2169/internalmedicine.8269-16
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mucosa-associated Lymphoid Tissue Lymphoma of the Trachea

Abstract: Mucosa-associated lymphoid tissue lymphoma is a common type of primary pulmonary carcinoma, but the presence of polypoid nodules is extremely rare. We herein report two cases with multiple nodules in the trachea. One case involved polypoid nodules and airway stenosis mimicking asthma; the other case had concurrent nontuberculous mycobacterial infection. The diagnosis of both cases was confirmed by bronchoscopy. The two cases were sensitive to radiotherapy and chemotherapy, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…A previous study reported that endobronchial MALT lymphoma was seen in only 1 (1.3%) of 75 cases of nongastrointestinal MALT lymphoma [ 5 ]. Including the present case, 28 cases [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ] in a PubMed search and 7 cases in Japanese journals of primary endobrochial MALT lymphoma have been reported.…”
Section: Discussionmentioning
confidence: 89%
“…A previous study reported that endobronchial MALT lymphoma was seen in only 1 (1.3%) of 75 cases of nongastrointestinal MALT lymphoma [ 5 ]. Including the present case, 28 cases [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ] in a PubMed search and 7 cases in Japanese journals of primary endobrochial MALT lymphoma have been reported.…”
Section: Discussionmentioning
confidence: 89%
“…На долю MALT-лимфом с поражением трахеобронхиального дерева приходится менее 0,5 % первичных злокачественных новообразований легких и менее 1 % всех лимфом [9]. Однако среди MALTлимфом легочные лимфомы встречаются в 19 %.…”
Section: Discussionunclassified
“…In human medicine, intraluminal tracheal B-cell lymphomas have often been characterized as mucosa associated lymphoid tissue (MALT) lymphomas. These are low-grade malignant neoplasias, which often remain localized and are generally associated with a favorable outcome [ 21 , 22 ]. In our case, the presence of the extraluminal tracheal mass adjacent to the intraluminal mass suggests a local invasive behavior (for example of a deep cervical lymph node), but there was no clear histological evidence of vascular or lymphatic invasion, and no further metastases could be detected.…”
Section: Discussionmentioning
confidence: 99%